PEGylated DOTA-AHA-based Gd(III) chelates – A relaxometric study - Fontes, André (2015)
Three PEGylated derivatives of 1,4,7,10-tetraazacyclododecane-1-((6-amino)hexanoic)-4,7,10-triacetic acid) (DOTA-AHA) with different molecular weights were prepared and characterized. Their Gd(III) chelates were studied in aqueous solution using variable-temperature 1H nuclear magnetic relaxation dispersion (NMRD) and 17ONMR spectroscopy in view of the determination of their relaxivity and the parameters that govern it. The relaxivity varied from 5.1 to 6.5 mM-1.s-1 (37 ºC and 60 MHz) with the increasing molecular weight of the PEG chain, being slightly higher than that of the parent chelate Gd(DOTA-AHA), due to a small contribution of a slow global rotation of the complexes. A variable temperature 1H NMR study of several Ln(III) chelates of DOTA-A(PEG750)HA allowed the determination of the isomeric M/m ratio (M = square antiprismatic isomer and m = twisted square antiprismatic isomer, the latter presenting a much faster water exchange) which for the Gd(III) chelate was estimated in circa 1:0.2, very close to that of [Gd(DOTA)]-. This explains why the PEGylated Gd(III) chelate has a water rate exchange similar to that of [Gd(DOTA)]-. The predominance of the M isomer is a consequence of the bulky PEG moiety which does not favor the stabilization of the m isomer in sterically crowded systems at the substituent site, contrary to what happens with less packed asymmetrical DOTA-type chelates with substitution in one of the four acetate C(α) atoms.